Natamycin efficiency for controlling yeast growth in models systems and on cheese surfaces - Ollé Resa, Carolina Patricia (2014)
Consumers demand for more natural ingredients in processed foods is a result of a requirement for more healthy and safe food with also a need for a balanced and adequate diet. Natamycin is a polyene macrolide antibiotic which is active against yeasts and moulds but not against bacteria, viruses and protozoa. In this study the effectiveness of natamycin delivered by different methods against Saccharomyces cerevisiae, Zygosaccharomyces rouxii and Yarrowia lipolytica using both food models and cheese with natural antimicrobials. It was observed that natamycin concentration and yeast type influenced whether the natamycin effect in tapioca starch films was cidal or inhibitory. This was also observed when the antimicrobial was applied directly to a liquid system for comparison purposes. Bioavailability was not compromised by the polymeric supporting matrix and natamycin efficiency against a S. cerevisiae contamination that preceded antimicrobial application was superior when film action was compared with spraying.